Optimasi pemenuhan zat gizi dan penyusunan menu untuk pencegahan kekurangan energi kronik pada wanita prakonsepsi - Putri, Febriani; Kandarina, BJ. Istiti; Helmyati, Siti (Jurnal Gizi Klinik Indonesia, 2024)
Optimization of nutritional fulfillment and menu recommendations to prevent chronic energy deficiency in preconception womenBackground: Chronic energy deficiency (CED) is a nutritional problem in Indonesia that occurs in women of childbearing age (WCA). This made them the group that must be given attention, especially nutrition, because they will be mothers. The Special Region of Yogyakarta is one province with a proportion of pregnant women with CED above the national average. Dietary intake patterns must be designed to comply with nutritional recommendations while maintaining the intake of specific local and cultural foods.Objective: This study aimed to analyze CED status, food intake, and diversity and develop menu recommendations to prevent chronic energy deficiency using linear programming.Methods: This research used cross-sectional sampling with a quota sampling method, which obtained 110 respondents. The interview was conducted using a 24-hour recall form and SQ-FFQ, and a menu was created to prevent CED.Results: There was no difference in the average food intake against CED (p-value>0.05). There was no difference in average between food diversity (p-value=0,48) and daily expenditure (p-value=0,95). This study recommended a menu in 7 days with a minimum price and a variety of food.Conclusions: There was no average difference between food intake, food diversity, and food expenditure on CED. This menu recommendation can be used for respondents who suffer from CED and those who do not suffer from CED by considering the nutrients that have been achieved.